Analysis of the Causes and Countermeasures for the "Fragile College Students" Phenomenon - Zhou, Yaqian (International Journal of Social Sciences and Public Administration, 2024)
Recently, the term "fragile college students" has gained popularity online, becoming a new label that many students identify with. The term refers to a new generation of college students who, despite their youth, suffer from numerous physical ailments and seem fragile, almost as if they would break at the slightest touch, exhibiting the so-called "fragile phenomenon." This phenomenon reflects irregular lifestyles and declining physical fitness among contemporary college students, exacerbated by the rapid iteration of external environments, which intensifies the toll on their well-being. The rise of “fragile college students” serves as a reminder to society and educational institutions to seriously address students’ irregular lifestyles, lack of exercise, unhealthy diets, and psychological issues. Suggestions include providing health education and psychological counseling, increasing sports facilities and venues, offering healthy dining options, and building a strong ideological foundation for youth to promote healthy growth.